Molecular and proteomic identification of Neoscytalidium dimidiatum as onychomycosis and dermatomycosis etiologic agent - Flórez-Muñoz, Sindy V. (2019)
[Excerpt] The Botryosphaeriaceae family includes genera frequently related with plant diseases. Nevertheless, human infections caused by fungal plant pathogens are becoming more frequent. Neoscytalidium species are mainly phytopathogenic but cases of phaeohyphomycosis have been reported. Within this genus. four species are currently recognized: N. dimidiatum, N. orchidacearum, N. novaehollandiae, and N. oculus. Although N. dimidiatum is frequently found in soil. it has been identified as an etiologic agent of onychomycosis or dermatomycosis. On the other hand, N. oculus was isolated and identified as an etiologic agent of an ocular lesion. All these species are very similar with regard to their macroscopic and microscopic traits, which lead to complex and imprecise identification based on morphological traits alone. [...]